Transformation of Community-Based Islamic Education in Building Family Resilience and Empowering Marginalized Communities - Kandiri Kandiri (Education and Sociedad Journal, 2025)
This study aims to analyze the transformation of community-based Islamic education in strengthening family resilience and empowering marginalized communities through a comprehensive review of relevant scholarly literature. The research employs a Systematic Literature Review (SLR) approach by identifying, selecting, and synthesizing articles, books, and scientific reports published in reputable national and international journals. The literature was analyzed using thematic analysis to identify patterns, strategies, challenges, and impacts of community-based Islamic education on family and social empowerment. The findings reveal that community-based Islamic education plays a strategic role in fostering family resilience through the internalization of Islamic values, character development, religious literacy, and strengthening interpersonal relationships within families. Furthermore, Islamic educational programs implemented through mosques, Islamic boarding schools, community learning centers, and religious organizations contribute significantly to enhancing social capital, economic independence, community participation, and social cohesion among marginalized groups. The review also indicates that successful programs are characterized by participatory approaches, local cultural adaptation, collaborative stakeholder engagement, and the integration of spiritual, social, and economic dimensions of empowerment. In conclusion, the transformation of community-based Islamic education serves as an effective instrument for strengthening family resilience and promoting sustainable community empowerment. The study implies that policymakers, educational institutions, and community organizations should develop more inclusive, participatory, and context-sensitive Islamic education models to address contemporary social challenges and improve the quality of life of marginalized communities.